2019
DOI: 10.1007/s10840-019-00683-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance for femoral venous access in electrophysiology procedures—systematic review and meta-analysis

Abstract: Purpose The most common complications of electrophysiology (EP) procedures are related to vascular access. Our study aims to conduct a meta-analysis comparing ultrasound (US)-guided vs. palpation-based technique for femoral venous access in EP procedures. Methods Electronic databases were searched and systematically reviewed for studies comparing femoral vein puncture with/ without US in EP procedures. The primary outcome was the rate of major vascular complications; secondary outcomes were minor vascular comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
3
32
0
1
Order By: Relevance
“…Another larger meta‐analysis demonstrated that the use of US‐guidance for vascular access in electrophysiology procedures reduces the risk of MVC by 71% compared with the standard anatomical approach 25 . Moreover US guidance significantly reduced puncture time and inadvertent arterial puncture 25 . Our results confirmed the benefit of US‐guidance in males only.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Another larger meta‐analysis demonstrated that the use of US‐guidance for vascular access in electrophysiology procedures reduces the risk of MVC by 71% compared with the standard anatomical approach 25 . Moreover US guidance significantly reduced puncture time and inadvertent arterial puncture 25 . Our results confirmed the benefit of US‐guidance in males only.…”
Section: Discussionsupporting
confidence: 74%
“…In a meta‐analysis by Sobolev et al, 24 the use of real‐time US‐guidance decreased access‐related bleeding and life‐threatening vascular complications, though the number needed to treat was quite large. Another larger meta‐analysis demonstrated that the use of US‐guidance for vascular access in electrophysiology procedures reduces the risk of MVC by 71% compared with the standard anatomical approach 25 . Moreover US guidance significantly reduced puncture time and inadvertent arterial puncture 25 .…”
Section: Discussionmentioning
confidence: 99%
“…A superior approach might increase the risk of retroperitoneal bleeding. A real‐time ultrasound‐guided venipuncture may be useful and recommended to prevent these vascular complications 10,11 . A meta‐analysis investigating the utility of ultrasound‐guided femoral venous access showed that this technique reduced major and minor vascular complications, inadvertent artery punctures, postprocedural groin pain, and puncture time as compared with the palpation‐based technique in electrophysiological procedures 10 .…”
Section: Discussionmentioning
confidence: 99%
“…A real‐time ultrasound‐guided venipuncture may be useful and recommended to prevent these vascular complications 10,11 . A meta‐analysis investigating the utility of ultrasound‐guided femoral venous access showed that this technique reduced major and minor vascular complications, inadvertent artery punctures, postprocedural groin pain, and puncture time as compared with the palpation‐based technique in electrophysiological procedures 10 . This technique also increased the first‐pass and overall success rates and reduced the risk of complications of central venous catheterization through the subclavian and femoral routes, as well as arterial and difficult peripheral venous access 11 .…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta-analysis found that the rate of vascular complications in electrophysiology procedures-and thus, major and minor bleeding-can be reduced by using ultrasound-guided femoral access. 30…”
Section: Bleeding Riskmentioning
confidence: 99%